Diagnostic Overview and Management of Adult Pulmonary Tuberculosis Patients Inpatient at RSU Royal Prima Medan in 2020 - Dewi Sartika; Nerseri Barus; Sri Lestari Ramadhani Nasution (HM Publisher, 2022)
Tuberculosis is an inflammatory disease of the lung parenchyma caused by infection with Mycobacterium tuberculosis. This research aims to find out the description of the diagnosis and management of adult pulmonary TB patients hospitalized at RSU Royal Prima Medan in 2020. This study is a descriptive study. This study is based on medical record data on inpatients with a diagnosis of pulmonary TB at the Royal Prima General Hospital Medan in 2020. The youngest patient was 18 years old and the oldest was 82 years old. The main complaint was shortness of breath (53%), additional complaints were cough (48%), symmetrical physical examination of the thorax (91%), positive sputum smear examination (72%), combined medical management of pulmicort + fumadryl + paracetamol + levofloxacin + OAT category I (72%), the longest length of stay was 7-8 days (38%), the shortest was 11-12 days (1%). In conclusion, pulmonary TB occurs more in men in the 37- 45 year age group (22%), the most complaints are shortness of breath (53%), and the most widely used combination treatment is pulmicort + fumadryl + paracetamol + levofloxacin + drugs anti tuberculosis category I (72%).